1968
DOI: 10.1161/01.res.23.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Valvular Regurgitation on the Oxygen Consumption of the Canine Heart

Abstract: The effects on myocardial oxygen consumption and mechanics of acute, simulated aortic and mitral regurgitation were studied in open-chest, anesthetized dogs to determine how changes in the mechanical performance of the ventricle alter oxygen consumption. When regurgitation was induced acutely with effective stroke volume (total stroke volume less regurgitant volume) and heart rate held constant, left ventricular end-diastolic volume, total stroke volume, the ejection fraction, left ventricular wall tension, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A current hypothesis is that flow is normally less in the subendocardium during systole due to this pressure gradient, but greater in the subendocardium during diastole due to autoregulation of flow by coronary resistance vessels (21) The previous studies raised an important question concerning the adequacy of subendocardial flow in aortic insufficiency, and one of the main purposes of the present investigation was to obtain information bearing on this question. It was felt that information on regional tissue flow would not permit a reliable assessment of the nutritional adequacy of such flow because oxygen consumption of the ventricle is reported to be increased in aortic insufficiency (14). Accordingly, metabolic data were sought that would reflect the balance between oxygen supply and demand in the inner and outer regions of the left ventricle in animals with aortic insufficiency.…”
Section: Methodsmentioning
confidence: 99%
“…A current hypothesis is that flow is normally less in the subendocardium during systole due to this pressure gradient, but greater in the subendocardium during diastole due to autoregulation of flow by coronary resistance vessels (21) The previous studies raised an important question concerning the adequacy of subendocardial flow in aortic insufficiency, and one of the main purposes of the present investigation was to obtain information bearing on this question. It was felt that information on regional tissue flow would not permit a reliable assessment of the nutritional adequacy of such flow because oxygen consumption of the ventricle is reported to be increased in aortic insufficiency (14). Accordingly, metabolic data were sought that would reflect the balance between oxygen supply and demand in the inner and outer regions of the left ventricle in animals with aortic insufficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Almost a century ago, Evans and Matsuoka 23 found that increased flow work added little to the energy requirements of the heart. Later, Urschel and associates 24 demonstrated that myocardial oxygen consumption increased only minimally during experimental MR, despite a doubling of the total stroke volume. Thus, the LV response to acute MR includes an increase in preload, a decrease in afterload, an increased EF, and an increased total stroke volume.…”
Section: Gaasch and Meyer Left Ventricular Response To Mitral Regurgimentioning
confidence: 99%
“…The Laplace law (wall stress = [pressure × radius]/2 × wall thickness) provides a useful framework for the understanding of hemodynamic changes in AR [4]. The acute volume overload forces the normal-sized LV to reach the limits of it preload reserve while imposing excessive afterload [5], resulting in marked increase in LV wall stress with resultant decrease in myocardial oxygen consumption [5,6]. This leads to acute afterload mismatch, causing acute depression in LV, ejection fraction (LVEF) [5].…”
Section: Acute Aortic Regurgitationmentioning
confidence: 99%